Rural Alaskan Youth's Attitudes Toward Education - Lily Chu; Jeanne Culbertson (Journal of Research in Rural Education, 1982)
This research examines rural Alaskan youth's educational expectations, aspirations, and anticipatory goal deflections. The subjects are seventy-three students from three rural schools with a variety of racial-ethnic backgrounds. Significant differences between groups and schools are reported. Implications for educational planning are discussed.